2005
DOI: 10.4049/jimmunol.175.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Novel Innate Immune Functions for Galectin-1: Galectin-1 Inhibits Cell Fusion by Nipah Virus Envelope Glycoproteins and Augments Dendritic Cell Secretion of Proinflammatory Cytokines

Abstract: Galectin-1 (gal-1), an endogenous lectin secreted by a variety of cell types, has pleiotropic immunomodulatory functions, including regulation of lymphocyte survival and cytokine secretion in autoimmune, transplant disease, and parasitic infection models. However, the role of gal-1 in viral infections is unknown. Nipah virus (NiV) is an emerging pathogen that causes severe, often fatal, febrile encephalitis. The primary targets of NiV are endothelial cells. NiV infection of endothelial cells results in cell-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
162
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 53 publications
1
162
0
2
Order By: Relevance
“…It has been demonstrated that galectin-1 inhibits envelope-mediated cell-cell fusion of some paramyxoviruses by binding to specific N-glycans on viral glycoproteins and inducing its oligomerization [27]. However, galectin-1 can also promote human immunodeficiency virus infectivity by stabilizing viral attachment to host cells and cross-linking viral glycoproteins with the target cells [28].…”
Section: Galectin-carbohydrate Lattices In Host-pathogen Interactionsmentioning
confidence: 99%
“…It has been demonstrated that galectin-1 inhibits envelope-mediated cell-cell fusion of some paramyxoviruses by binding to specific N-glycans on viral glycoproteins and inducing its oligomerization [27]. However, galectin-1 can also promote human immunodeficiency virus infectivity by stabilizing viral attachment to host cells and cross-linking viral glycoproteins with the target cells [28].…”
Section: Galectin-carbohydrate Lattices In Host-pathogen Interactionsmentioning
confidence: 99%
“…Pseudotyped VSV viruses were prepared and assayed for infection as previously described (26,(29)(30)(31). Unless indicated otherwise, all infections were performed in 1% FBS in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Galectins are PRRs in several types of organisms, and many mammalian pathogens express saccharide structures that are recognized by galectins. Galectin-1 binds saccharide ligands on envelope glycoproteins of Nipah virus and HIV (20,21). Galectin-3 and galectin-9 bind Leishmania major and galectin-9 promotes L. major-macrophage interactions (22,23).…”
mentioning
confidence: 99%